Recent Progress in Electrochemical Sensors for Environmental Monitoring - Melly Angglena; Khalil Zaman; Zara Ali (Research of Scientia Naturalis, 2024)
The increasing demand for real-time monitoring of environmental pollutants has driven advancements in electrochemical sensors. These sensors offer high sensitivity, selectivity, and the ability to operate in diverse conditions, making them ideal for environmental applications. Recent developments in materials and technologies have further enhanced their performance. This research aims to review the latest advancements in electrochemical sensors specifically designed for environmental monitoring. The focus is on evaluating their effectiveness in detecting various pollutants, including heavy metals, pesticides, and gases. A systematic literature review was conducted, analyzing recent studies and innovations in electrochemical sensor technology. Key parameters such as sensitivity, detection limits, and response times were compared across different sensor types. Advances in nanomaterials and miniaturization techniques were also examined to assess their impact on sensor performance. The findings indicate significant improvements in electrochemical sensors, with many achieving detection limits in the nanomolar range. Sensors utilizing nanostructured materials demonstrated enhanced sensitivity and faster response times. Additionally, the integration of wireless technologies allows for real-time data transmission, facilitating more efficient environmental monitoring. Recent progress in electrochemical sensors represents a vital advancement in environmental monitoring technology. These sensors offer promising solutions for detecting pollutants with high precision and reliability. Future research should focus on further improving sensor robustness and expanding their applicability across various environmental contexts.